The Living Kidney Donor Safety Study: Protocol of a Prospective Cohort Study. (October 2022) - Garg, Amit X.; Arnold, Jennifer B.; Cuerden, Meaghan; Dipchand, Christine; Feldman, Liane S.; Gill, John S.; Karpinski, Martin; Klarenbach, Scott; Knoll, Greg A.; Lok, Charmaine; Miller, Matthew; Monroy-Cuadros, Mauricio; et al.
Background: Living kidney donation is considered generally safe in healthy individuals; however, there is a need to better understand the long-term effects of donation on blood pressure and kidney function. Objectives: To determine the risk of hypertension in healthy, normotensive adults who donate a kidney compared with healthy, normotensive non-donors with similar indicators of baseline health. We will also compare the 2 groups on the rate of decline in kidney function, the risk of albuminuria, and changes in health-related quality of life. Design, Participants, and Setting: Prospective cohort study of 1042 living kidney donors recruited before surgery from 17 transplant centers (12 in Canada and 5 in Australia) between 2004 and 2014. Non-donor participants (n = 396) included relatives or friends of the donor, or donor candidates who were ineligible to donate due to blood group or cross-match incompatibility. Follow-up will continue until 2021, and the main analysis will be performed in 2022. The anticipated median (25th, 75th percentile, maximum) follow-up time after donation is 7 years (6, 8, 15). Measurements: Donors and non-donors completed the same schedule of measurements at baseline and follow-up (non-donors were assigned a simulated nephrectomy date). Annual measurements were obtained for blood pressure, estimated glomerular filtration rate (eGFR), albuminuria, patient-reported health-related quality of life, and general health. Outcomes: Incident hypertension (a systolic/diastolic blood pressure ≥ 140/90 mm Hg or receipt of anti-hypertensive medication) will be adjudicated by a physician blinded to the participant's donation status. We will assess the rate of change in eGFR starting from 12 months after the nephrectomy date and the proportion who develop an albumin-to-creatinine ratio ≥3 mg/mmol (≥30 mg/g) in follow-up. Health-related quality of life will be assessed using the 36-item RAND health survey and the Beck Anxiety and Depression inventories. Limitations: Donation-attributable hypertension may not manifest until decades after donation. Conclusion: This prospective cohort study will estimate the attributable risk of hypertension and other health outcomes after living kidney donation.